Transformation of 5-acylated N-fluoroalkyl-1,2,3-triazoles to trifluoromethylated ring-fused isoquinolines, 1,3-oxazines, and 1,3-oxazin-6-ones via ketenimines - Janecký, Lukáš; Klepetářová, Blanka; Beier, Petr (RSC advances, 2024)
A one-pot multistep methodology leading to trifluoromethylated cyclopenta[c]isoquinolines, indeno[1,2-c]isoquinolines, 6,6-difluoro-1,3-oxazines, or 1,3-oxazin-6-ones, based on the reaction of 5-acylated N-pentafluoroethyl-substituted 1,2,3-triazoles is presented. A thermal ring opening of the starting triazoles, followed by a 1,2-acyl shift formed reactive ketenimines which cyclized after a rearrangement in a substrate-specific manner to provide new trifluoromethylated heterocyclic products.